The Influence of Policies on Trade and Foreign Direct Investment - Golub, Stephen S.. (OECD Publishing, 2003)
This paper assesses the importance of border and non-border policies for global economic integration. The focus is on four widely-advocated policies: removing explicit restrictions to trade and FDI; promoting domestic competition; improving the adaptability of labour markets; and ensuring adequate levels of infrastructure capital. The analysis covers FDI and trade in both goods and services, thus aiming to account for the most important channels of globalisation and dealing with most modes of cross-border services supply. The results highlight that, despite extensive liberalisation over the past two decades, there is scope for further reducing policy barriers to integration of OECD markets. Remaining barriers have a significant impact on bilateral trade and FDI, with anticompetitive domestic regulations and restrictive labour market arrangements estimated to curb integration as much as explicit trade and FDI restrictions. Simulating the removal of such barriers suggests that the quantitative effects of further liberalisation of trade, FDI and domestic product and labour markets on global integration could be substantial...
Keywords: Economics